Psychological Dynamics and Strategies to Overcome Problems Among Generation Z Students Experiencing Academic Fatigue - Fira Dwiana Nuriska; Naufal Ahmad Rijalul Alam (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
Academic burnout is a psychological challenge experienced by many Generation Z students, especially in their final semester when they are faced with the pressures of writing a thesis, graduation goals, and interrelated academic and personal demands. This study aims to explore in depth the psychological dynamics and coping strategies used by Generation Z students in dealing with academic burnout. This study used a descriptive qualitative approach with four informants, final semester students from various study programs at Muhammadiyah University of Yogyakarta, selected through a purposive sampling technique. Data were collected through in-depth semi-structured interviews and analyzed using the Miles and Huberman interactive model. The results show that academic burnout in Generation Z students is multidimensional, triggered by the pressure of completing a thesis, social comparison with peers, academic role conflict, and accumulated personal and family demands. In dealing with it, informants use four forms of coping strategies: problem-focused coping, emotion-focused coping, avoidance coping, and religious-spiritual coping, which are used flexibly according to each individual's assessment of the situation at hand. In addition, social support from family and friends, as well as internal motivation, play a role in helping students cope with academic stress. This study makes a theoretical contribution by expanding the understanding of stress coping mechanisms beyond the Lazarus and Folkman framework by adding spiritual and cultural dimensions, as well as a practical contribution to the development of mental health support services in higher education settings.